THE EFFECT OF HEALTH CONSCIOUSNESS, FOOD SAFETY CONCERN, AND PRICE PERCEPTION ON ORGANIC MEAT PURCHASE INTENTION: THE MEDIATING ROLE OF CONSUMER ATTITUDE AMONG GENERATION Z - Nathania, Ailin Rosa; Rohman, Fatchur; Susilowati, Christin (Faculty of Administrative Science, Universitas Brawijaya, 2026)
This study aims to analyze the influence of health awareness, food safety concerns, and price perception on the intention to purchase organic meat among Generation Z in Malang City, with consumer attitude as the mediating variable. This study employed a quantitative approach using a survey method by distributing questionnaires to Generation Z respondents familiar with organic meat products. A total of 206 data points were collected, of which 164 were deemed valid and used in the analysis. The data analysis technique employed was Partial Least Squares Structural Equation Modeling. The results indicate that health consciousness, food safety concerns, and price perception significantly influence consumer attitudes. Furthermore, these three variables also significantly influence purchase intention, both directly and through the mediation of consumer attitudes. Consumer attitudes were found to play a crucial role as a mediating variable in strengthening the relationship between the independent variables and purchase intention. These findings suggest that the decision to purchase organic meat is not formed directly but rather through a prior cognitive and affective evaluation process by consumers. Overall, the results of this study indicate that consumer attitudes are a key factor in explaining the purchase intention of organic meat among Generation Z in Malang City. Therefore, increasing health awareness, ensuring food safety, and fostering a positive perception of value can strengthen consumer attitudes and encourage an increase in the purchase intention of organic meat products